Writing Matters. Presenting and Perceiving Monumental Inscriptions in Antiquity and the Middle Ages - Stroth, Fabian (Materiale Textkulturen, 2017)
This edited volume includes a compilation of new approaches to the investigation of inscriptions from different cultural contexts. Innovative research questions about "material text cultures" are examined with reference to Classical Athens, late ancient and Byzantine churches and urban spaces, Hellenistic and Roman cities, and medieval buildings.